Sinergitas antara Keluarga dan Guru Serta Gereja dalam Menanggulangi Kemerosotan Moralitas Anak di Era Modernisasi - Rapi Gultom (PNEUMATIKOS: Jurnal Teologi Kependetaan, 2022)
Abstract: In this era of modernization, synergy between families, teachers and churches is needed intackling the decline of children's morality to prevent children from the negative impacts of thismodernization. There are many teenagers in this modernization era who no longer have manners andrespect for older people and even behave badly by committing immoral and criminal acts. Because of thenegative impact of modernization. This study uses a qualitative descriptive method by using books andother reading materials. The focus is on the synergy between the family and the church in overcoming the decline in the morality of children in the era of modernization. The results obtained by researchers from thisstudy are that there is a synergy between the family and the church through a psychological approach and atheological approach. The psychological approach is done through counseling and seminars. The theologicalapproach is carried out through Bible Camps and Retreats. However, from the results of the study, there arestill children who are negatively affected by modernization due to the influence of bad associations fromschool friends and friends. That is why families and churches must constantly strive to educate theirchildren well in order to avoid the negative effects of modernization.